390 The PIPAH Study: a new prospective study of pesticide applicators. (11th October 2013) - Harding, Ah; Frost,; Chen,; Boorman,; Pearce,; Fishwick,
Abstract : Objectives: The PIPAH Study, a new prospective study of professional pesticide applicators in Great Britain is being established. The objectives of the study will be to monitor the long-term health of these pesticide applicators and to investigate associations between health outcomes and occupational exposure to pesticides. Methods: The 21, 000 members of two national registers of professional pesticide applicators will be invited to participate in the study. The schedule of reminders includes a postcard sent to all potential participants shortly after the initial invitation, an article in the trade journal for pesticide applicators, and a full study pack sent to non-responders. Those who agree to participate will complete a general questionnaire covering their work history, previous pesticide usage, personal and family medical history, signs/symptoms of neurological disease, socioeconomic factors, diet and lifestyle. This can be completed using the paper questionnaire sent to them or online. New members of the two registers will be invited to participate in the study in a rolling recruitment programme. Participants will be flagged for notification of all cancer and death registrations, and hospital episode statistics for particular health conditions. More detailed pesticide exposure data will be collected annually, beginning in December 2013. Results: The baseline data will be analysed to provide summary data describing the characteristics of the new cohort. Descriptive statistics will include basic demographics, regional distribution, and summaries of pesticide exposures and lifestyle factors. Response rates, the effect of reminders, the proportion responding online, and factors associated with online response will be presented. Conclusions: This cohort study will play an important role in the post-marketing surveillance of ill-health among professional pesticide applicators in Britain. It will also provide a resource for more detailed investigation of specific health outcomes and exposures.